Conditional cash transfers and child labor - Cepaluni, Gabriel [UNESP]; Chewning, Taylor Kinsley; Driscoll, Amanda; Faganello, Marco Antonio (Elsevier, 2022)
Child labor is a pernicious problem throughout the developing world, but conditional cash transfer programs (CCTs) could reduce the number of working children. We evaluate the effectiveness of CCTs at attenuating child labor based on our analysis of a massive administrative dataset on Brazil's applicants to social programs between 2001 and 2015. We use Multiples (twins, triplets, etc.) as an instrument for receiving the Bolsa Família stipend. Receiving the stipend does not offset the cost of an exogenous increase in family size, does not reduce child laborers’ participation in the workforce and does not improve educational outcomes for child laborers in households with Multiples births. Instead, contextual and familial factors appear to shape program efficacy in mitigating this troubling practice.
Keywords: Child labor; Conditional cash transfers; Developing world; Poverty